B-VALUE AND SLIP RATE SENSITIVITY ANALYSIS FOR PGA VALUE IN LEMBANG FAULT AND CIMANDIRI FAULT AREA - PRATAMA (NIM : 22410501); Pembimbing: Dr. Irwan Meilano ; Dr. Andri Dian Nugraha, CECEP
There is many different result of slip rate and b-value from different method or limiting assumption. Slip rate and b-value are used to estimate earthquake recurrence relationship which is the most influence for hazard level. We found variation of slip rate and b-value result for Lembang-Cimandiri fault and West Java seismicity, respectively. We examine slip rate and b-value contribution of Peak Ground Acceleration (PGA) in probabilistic seismic hazard maps (10% probability of exceedence in 50 years or 500 years return period). Hazard curves of PGA have been investigated for Sukabumi and Bandung using a PSHA (Probabilistic Seismic Hazard Analysis). We observe that the most influence in the hazard estimate is crustal fault.Monte Carlo approach has been developed to assess the sensitivity. Uncertainty and coefficient of variation from slip rate and b-value in Lembang and Cimandiri Fault area have been calculated. We observe that seismic hazard estimates is sensitive to fault slip rate and b-value with uncertainty result are 0.25 g dan 0.1-0.2 g, respectively. For specific site, we found seismic hazard estimate are 0.49 + 0.13 g with COV 27% and 0.39 + 0.05 g with COV 13% for Sukabumi and Bandung, respectively.